Continuing utilisation of specialised health services in extremely preterm infants. Issue 5 (5th August 2010) - Luu, T M; Lefebvre, F; Riley, P; Infante-Rivard, C
Abstract : Objective: To compare healthcare use from neonatal discharge to 18 months corrected age (CA) of two groups of extremely preterm neonates (23–25 vs 26–28 weeks). Design: Cohort study. Patients: Infants born at ≤28 weeks and admitted in three hospital centres in Quebec, Canada (n=254). Main outcome measures: Neurodevelopmental outcomes and healthcare use from neonatal discharge to 18 months CA. Results: Re-hospitalisation rates occurred in 57% of children born at 23–25 weeks and in 49% of those born at 26–28 weeks. In these two age groups, by 18 months, 61% vs 59% were followed in physical or occupational therapy, 29% vs 17% were enrolled in a long-term rehabilitation program, 38% vs 28% used prescribed medication, and 59% vs 33% required medical assistive devices, respectively. Risk of re-hospitalisation was related to bronchopulmonary dysplasia (BPD), severe brain injury, use of home oxygen or an apnoea monitor and older age at neonatal discharge. Multiple births, BPD, severe brain injury, older age at neonatal discharge and single parenthood were associated with risk of using out-patient health services above average (>2 services). Conclusion: Extremely preterm children are frequently re-hospitalised during infancy and use a substantial amount of healthcare resources. These results highlight the importance of resource allocation to preterm infants for medical and rehabilitation services after discharge from the neonatal intensive care unit.